Safety assessment of anti-B cell maturation antigen chimeric antigen receptor T cell therapy: a real-world study based on the FDA adverse event reporting system database - Liu, Wei; Lin, Shuzhi; Zhu, Xiaoying; Yin, Lin; Liu, Qian; Lei, Shuang; Feng, Bianling (Frontiers in Immunology, 2024)
Background: On April 18, 2024, the U.S. Food and Drug Administration officially required updating of the "boxed warning" for T cell malignancies for all chimeric antigen receptor T cell (CAR-T) therapies. Given the clinical significance of these therapies, a rigorous safety assessment is paramount. However, comprehensive realworld safety studies have been lacking for the newly marketed CAR-T products idecabtagene vicleucel (ide-cel) and ciltacabtagene autoleucel (cilta-cel), which target B cell maturation antigen, especially regarding the risk of secondary malignancies.Therefore, we aimed to thoroughly analyze the adverse events (AEs) information in the FDA Adverse Event Reporting System (FAERS) database to comprehensively understand the safety risks of ide-cel and cilta-cel.We extracted AE reports related to ide-cel and cilta-cel from the FAERS database (https://fis.fda.gov/extensions/FPD-QDE-FAERS/FPD-QDE-FAERS.html.) from January 1, 2019 to December 31, 2023. Disproportionality analysis and Bayesian analysis were used to identify risk signals across subgroups and specific cases (including for death and secondary malignancies). Weibull distribution analysis was employed to determine the time to AE onset.Results: A total of 695 AE reports for ide-cel and 848 for cilta-cel were included in the FAERS database. This analysis identified 81 positive signals for ide-cel and 74 for ciltacel. Notably, comparisons with the drug labels revealed "unexpected signals," including febrile bone marrow aplasia (reporting odds ratio=69.10; confidence interval 39.12-122.03) and plasma cell myeloma (12.45; 8.18-18.95) for ide-cel, and increased serum ferritin (24.98; 8.0-77.58) and large intestine perforation (18.57; 5.98-57.69) for ciltacel. Both drugs showed a higher AE incidence among male recipients and patients aged ≥65 years, although female recipients faced a greater risk. Most AEs occurred at the early stage of administration. However, secondary malignancies were detected for both drugs, primarily occurring one year post-administration.This study provides a foundation for understanding the safety profile of CAR-T cell therapy, particularly in relation to the emergence of secondary malignancies. Such insights are helpful for clinical decision-making and the safe and effective utilization of these therapeutic agents.